Circulating extra-cellular RNAs and atrial fibrillation: data from the TRACE-CORE cohort - Katherine Tak; Darleen Lessard; Catarina I. Kiefe; Jane E. Freedman; Matthew Parker; Gerard P. Aurigemma; Kevin Donahue; David D. McManus; David D. McManus; Khanh-Van Tran (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAtrial fibrillation (AF) is the most common sustained arrhythmia and is linked to increased risk of stroke, heart failure, and mortality. Circulating extracellular RNAs (exRNAs), which regulate gene expression and reflect underlying biological processes, are potential biomarkers for atrial fibrillation.MethodsAs part of an ongoing, larger study into extracellular RNAs (exRNAs) as potential biomarkers for cardiovascular disease, we analyzed exRNA profiles in a subset of 296 survivors of acute coronary syndrome (ACS) enrolled in the Transitions, Risks, and Actions in Coronary Events Center for Outcomes Research and Education (TRACE-CORE) cohort. A total of 318 exRNAs were quantified, selected a priori based on prior findings from the Framingham Heart Study. We assessed associations between circulating exRNAs and echocardiographic intermediate phenotypes relevant to atrial fibrillation (AF), including left atrial dimension, left ventricular (LV) mass, LV end-diastolic volume, and global longitudinal strain. Subsequently, we used logistic regression models to evaluate whether the exRNAs associated with these phenotypes were also associated with a history of AF (n = 18, 5.4%). Downstream bioinformatics analyses were performed to identify putative target genes, enriched gene ontology categories, and molecular pathways regulated by these candidate microRNAs.ResultsWe identified 77 extracellular RNAs (exRNAs) that were significantly associated with increased left ventricular (LV) mass and at least one additional echocardiographic intermediate phenotype. Among these, miR-17-5p and miR-574-3p were also significantly associated with a history of atrial fibrillation (AF), with odds ratios of 1.58 (95% CI: 1.10–2.26) and 2.16 (95% CI: 1.03–4.54), respectively. Predicted gene targets of these miRNAs were enriched in pathways implicated in atrial remodeling and arrhythmogenesis. Key overlapping canonical pathways included the Senescence Pathway, Idiopathic Pulmonary Fibrosis Signaling, ERK5 Signaling, RHO GTPase Cycle, and HGF Signaling.ConclusionsCirculating exRNAs, including miR-17-5p and miR-574-3p, are associated with cardiac remodeling and a history of AF in ACS survivors. These findings highlight their potential as biomarkers of atrial remodeling and implicate key molecular pathways involved in AF pathogenesis.